Stereotypes and Prejudice in American Born Chinese - Dlabová, Lucie (Univerzita Pardubice, 2024)
The work deals with a cultural-historical context of Asian Americans, focusing on the legislation that influenced the lives of Asian immigrants, the Asian immigration waves and general relationships between Americans and Asian immigrants throughout history. Furthermore, this thesis focuses on the analysis of stereotypes and prejudice which influence the lives of the Chinese in the graphic novel American Born Chinese by Gene Luen Yang. This graphic novel is also discussed in terms of Asian American literary context where other Asian-American authors are mentioned.
Stereotypy a předsudky v grafickém románu Američan čínského původu
Keywords: stereotypy; předsudky; asijská migrace; Číňané; Američan čínského původu; stereotypes; prejudice; Asian immigration; the Chinese; American Born Chinese